Efficacy and Safety of Drug-Eluting Stents in the Real World: 8-Year Follow-Up - Pellegrini,Denise Oliveira (2014)
Background: Drug-eluting stents have been used in daily practice since 2002, with the clear advantages of reducing the risk of target vessel revascularization and an impressive reduction in restenosis rate by 50%-70%. However, the occurrence of a late thrombosis can compromise long-term results, particularly if the risks of this event were sustained. In this context, a registry of clinical cases gains special value. Objective: To evaluate the efficacy and safety of drug-eluting stents in the real world. Methods: We report on the clinical findings and 8-year follow-up parameters of all patients that underwent percutaneous coronary intervention with a drug-eluting stent from January 2002 to April 2007. Drug-eluting stents were used in accordance with the clinical and interventional cardiologist decision and availability of the stent. Results: A total of 611 patients were included, and clinical follow-up of up to 8 years was obtained for 96.2% of the patients. Total mortality was 8.7% and nonfatal infarctions occurred in 4.3% of the cases. Target vessel revascularization occurred in 12.4% of the cases, and target lesion revascularization occurred in 8% of the cases. The rate of stent thrombosis was 2.1%. There were no new episodes of stent thrombosis after the fifth year of follow-up. Comparative subanalysis showed no outcome differences between the different types of stents used, including Cypher®, Taxus®, and Endeavor®. Conclusion: These findings indicate that drug-eluting stents remain safe and effective at very long-term follow-up. Patients in the "real world" may benefit from drug-eluting stenting with excellent, long-term results.